EFEKTIVITAS FLIPPED CLASSROOM TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI MAHASISWA PGSD PADA MATA KULIAH MEDIA PEMBELAJARAN - Amril, Amril (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The aim of the study was to determine the high-level thinking skills of PGSD students at Dharmas Indonesia University in learning media courses by applying the flipped classroom model. The desired results test the effectiveness of the flipped classroom model in learning media courses on students' analytical, evaluation and creative abilities. Type of R&D research with ADDIE development procedure. The results showed that the effectiveness of the flipped classroom model in the learning activities of learning media courses for PGSD students at Dharmas Indonesia University had an average of 1.84. on the ability to analyze, the average is 1.84 on the ability to evaluate and the average is 1.09 on the ability to create. Testing the effectiveness of the model was carried out using the Mann-Whitney non-parametric statistical analysis test obtaining a significance level of 0.002 for the ability to analyze, 0.007 for the ability to evaluate and 0.008 for the ability to create. These values are less than 0.05, which means that the flipped classroom model implemented is able to improve the ability to analyze, evaluate and create the ability of PGSD students at Dharmas Indonesia University